Modified optical OR and AND gates - Srinivasulu, Avireni (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
This paper deals with optical OR and AND gate, using unijunction transistor (UJT), light emitting diode (LED), and photo-resistor (LDR). Effort is made to extend the development of the gates using UJT, LDR, and LED to work at 1.8 Vdc instead of 3 Vdc. The power dissipation is approximately 2 mW. These optical gates find application in the field of instrumentation, optical logic isolators, and fiber optics systems where intrinsic safety is of prime importance rather than speed of operation.